A Call to Action in Revolutionizing Student Mindsets: Empowering Environmental Consciousness Through Organic Farming Practices - Citra Irawan, Norbertus; Muqqorobin, Bagus Mustika Ali; Kusuma, Havit Aryan; Pratama, Ilham Gusni; Supriyadi, Teguh; Soelistijono, R (Journal of Community Capacity Empowerment, 2025)
This community service project was initiated in response to the growing concern about declining environmental awareness among high school students and the urgent need for sustainable practices. Given the limited study on effective interventions to foster environmental consciousness in this demographic, this study aimed to fill this gap by investigating the impact of a comprehensive organic farming program. The study employed a mixed-methods approach, combining quantitative surveys and qualitative interviews to assess changes in students’ knowledge, attitudes, and behaviors. Results indicated a significant increase in students’ understanding of organic farming principles, a positive shift in their attitudes towards sustainability, and a heightened sense of agency to implement sustainable practices daily. These findings highlight the potential of experiential learning and community engagement in promoting environmental stewardship among youth. Implications for educational policy, community development, and future study are discussed.